A Grid Fusion Lifting Surface and Its Flow Control Mechanism at High Angles of Attack - Fan Hua-yu; Mi Bai-gang; Liu Han-yu; Yu Jing-yi (International Journal of Aerospace Engineering)
A grid fusion lifting surface suitable for large subsonic angles of attack was designed. The influence of the grid position, grid diversion angle, and grid number on the aerodynamic performance of the grid fusion lifting surface under subsonic conditions was studied by numerical simulations. Based on the summary and analysis of the grid in the hypersonic state, the CFD numerical simulation method, which solves unsteady Reynolds averaged Navier-Stokes equations, was used to complete the research of the flow mechanism of the grid fin in the subsonic state. At low speed and subsonic conditions, the results show that the negative front grid fusion lift surface has better aerodynamic characteristics with a high angle of attack. Under subsonic conditions, the stall angle of attack of the front grid fusion lifting surface with a diversion angle of 20° increases by 16°, and the maximum lift coefficient increases by 22.1% compared to that of the conventional flat wing. The number of grids has an insignificant effect on the aerodynamic performance of the grid fusion lifting surface at a large angle of attack.